Promoting children’s cycling through cycling courses in city traffic (practice paper). - Mellauner, Marlene (My University, 2020)
To promote children’s cycling in Vienna the non-profit organization “Schulterblick –the Viennese Cycling School” has developed a unique road safety and mobility management program. It is based on the idea that children need to practise in real life traffic situations in order to be well prepared for cycling in urban traffic. The main educational goal is to promote a new cycling culture which contributes to a cooperative atmosphere between road users (a side-by-side city traffic). Based on the Schulterblick concept the association has been organizing on-road cycling courses for school classes in the city centre of Vienna since 2015. About 1.500 children aged 9 to 11, their teachers, parents and grandparents took part in 63 Schulterblick cycling courses. In addition, Schulterblick initiated a discussion between stakeholders about the importance of high-quality cycling courses and the potential of cycling education measures for a successful transition towards active mobility. Since 2016 their activities and achievements are gaining broader attention. Nevertheless, the success is accompanied by challenges concerning the positioning and long-term implementation.
Keywords: Kind; Fahrradverkehr; Unterricht; Verkehrssicherheit; Straßenverkehr; Stadtverkehr